A Retrospective Estimate of Ear Disease Detection Using the "Red Flags" in a Clinical Sample. Issue 5 (September 2018) - Klyn, Niall A. M.; Kleindienst Robler, Samantha; Alfakir, Razan; Nielsen, Donald W.; Griffith, James W.; Carlson, Deborah L.; Lundy, Larry; Dhar, Sumitrajit; Zapala, David A.
Abstract : Objectives: The purpose of this study was to evaluate the specificity and sensitivity of two red flag protocols in detecting ear diseases associated with changes in hearing. Design: The presence of red-flag symptoms was determined in a chart review of 307 adult patients from the Mayo Clinic Florida Departments of Otorhinolaryngology and Audiology. Participants formed a convenience sample recruited for a separate study. Neurotologist diagnosis was the criterion for comparisons. Results: Of the 251 patient files retained for analysis, 191 had one or more targeted diseases and 60 had age- or noise-related hearing loss. Food and Drug Administration red flags sensitivity was 91% (confidence interval [CI], 86 to 95%) and specificity was 72% (CI, 59 to 83%). American Academy of Otolaryngology-Head and Neck Surgery red flags sensitivity was 98% (CI, 95 to 99%) and specificity was 20% (CI, 11 to 32%). Conclusions: Stakeholders must determine which diseases are meaningful contraindications for hearing aid use and whether these red-flag protocols have acceptable levels of sensitivity and specificity. As direct-to-consumer models of hearing devices increase, a disease detection method that does not require provider intercession would be useful. Abstract : Supplemental Digital Content is available in the text.